2013
DOI: 10.1016/j.ijrobp.2013.06.2042
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Amplitude-Based and Phase-Based Positron Emission Tomography Gating Algorithms for Segmentation of Internal Target Volumes of Tumors Subject to Respiratory Motion

Abstract: Purpose To compare quantitatively the accuracy of tumor volume segmentation in amplitude-based and phase-based respiratory gating algorithms in respiratory-correlated positron emission tomography (PET). Methods and Materials List-mode fluorodeoxyglucose-PET data was acquired for 10 patients with a total of 12 fluorodeoxyglucose-avid tumors and 9 lymph nodes. Additionally, a phantom experiment was performed in which 4 acrylic spheres with inner diameters ranging from 1 to 4 cm were imaged as they underwent 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…The PET datasets corresponding to each individual interval or bin are noisier because of the lower counts per bin. The use of internal target volumes (ITVs) defined from respiratory‐gated PET/CT ITVs from amplitude binning has been shown to be larger and more accurate than those from phase binning . Amplitude and phase binning are achieved by subdividing a respiratory signal that is typically obtained from external hardware attached to the patient .…”
Section: Current Usage Of [18f]fdg‐pet In Rtmentioning
confidence: 99%
See 1 more Smart Citation
“…The PET datasets corresponding to each individual interval or bin are noisier because of the lower counts per bin. The use of internal target volumes (ITVs) defined from respiratory‐gated PET/CT ITVs from amplitude binning has been shown to be larger and more accurate than those from phase binning . Amplitude and phase binning are achieved by subdividing a respiratory signal that is typically obtained from external hardware attached to the patient .…”
Section: Current Usage Of [18f]fdg‐pet In Rtmentioning
confidence: 99%
“…The use of internal target volumes (ITVs) defined from respiratorygated PET/CT ITVs from amplitude binning has been shown to be larger and more accurate than those from phase binning. 117 Amplitude and phase binning are achieved by subdividing a respiratory signal that is typically obtained from external hardware attached to the patient. 118 However, the respiratory signal may also be generated using a datadriven approach, from motion information contained in the PET/CT data.…”
Section: C4 Respiratory Gatingmentioning
confidence: 99%
“…Internal organ movement has a degrading effect on image quality and quantitative values in terms of spatial resolution and contrast [6]. Respiratory gating is a technique for improving the measurement of lesion uptake and tumor volume in PET/CT [7]. Motion management is becoming an important issue in both diagnostic and therapeutic applications.…”
mentioning
confidence: 99%
“…terns are a common occurrence in PET imaging. [80,111,[136][137][138] Others also report that this may cause errors when binning the data into the appropriate respiratory gate. [138] PeTrack has an advantage over the RPM system with respect to its robustness to baseline shifts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this type of gating performs worse than amplitude based gating. [111,137,138] administration (see Figure 5.5(a)). A case study such as Anon4886 might prove more challenging due to the smaller amplitude of motion.…”
Section: Discussionmentioning
confidence: 99%